A gynandromorph of Xylocopa augusti and an unusual record of X. iris from Brazil (Hymenoptera: Apidae: Xylocopini) - Lucía, Mariano (2015)
Fil: Lucía, Mariano. División Entomología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina